Association of musculoskeletal pain in other body parts with new-onset shoulder pain: a longitudinal study among survivors of the Great East Japan Earthquake. Issue 2 (15th February 2021) - Hagiwara, Yoshihiro; Yabe, Yutaka; Sekiguchi, Takuya; Sugawara, Yumi; Tsuchiya, Masahiro; Yoshida, Shinichirou; Onoki, Takahiro; Takahashi, Tadahisa; Iwatsu, Jun; Tsuji, Ichiro; Itoi, Eiji
Abstract : Objective: Shoulder pain is a common health problem coexisting with other musculoskeletal pain. However, the effects of pre-existing musculoskeletal pain on the development of shoulder pain are not clear. The present study aimed to elucidate the association between coexisting musculoskeletal pain at other body sites and new-onset shoulder pain among survivors of the Great East Japan Earthquake (GEJE). Design: This is a longitudinal study. Setting: The study was conducted at the severely damaged coastal areas in Ishinomaki and Sendai cities. Participants: The survivors who did not have shoulder pain at 3 years after the GEJE were followed up 1 year later (n=2131). Interventions: Musculoskeletal pain (low back, hand and/or foot, knee, shoulder and neck pain) was assessed using self-reported questionnaires. Main outcome measures: The outcome of interest was new-onset shoulder pain, which was defined as shoulder pain absent at 3 years but present at 4 years after the disaster. The main predictive factor for new-onset shoulder pain was musculoskeletal pain in other body parts at 3 years after the GEJE; this was categorised according to the number of pain sites (0, 1, ≥2). Multiple regression analyses were conducted to calculate the odds ratio (OR) and 95% confidence interval (CI) for new-onset shoulder pain due to musculoskeletal pain in other body parts. Results: The incidence of new-onset shoulder pain was 6.7% (143/2131). Musculoskeletal pain in other body parts was significantly associated with new-onset shoulder pain. Using the survivors without other musculoskeletal pain as reference, the adjusted OR and 95% CI for new-onset shoulder pain were 1.86 (1.18 to 2.94) for those with one body part and 3.22 (2.08 to 4.98) for those with ≥2 body parts presenting with musculoskeletal pain (p<0.001). Conclusions: Pre-existing musculoskeletal pain in other body parts was significantly associated with new-onset shoulder pain among survivors; this provides useful information for clinical and public health policies.